Association of bovine insulin-like growth factor-I receptor polymorphism gene with milk production traits in Iranian Najdi and Holstein dairy cows - Bakhtari, A.; Rahmani, H. R.; Edriss, M. A.; Sayed-Tabatabaei, B. E. (Cuban Journal of Agricultural Science, 2010)
In the present study, 266 Holstein cows (Bos taurus) and 41 Najdi cows (Bos indicus) were selected randomly used to estimate polymorphism in the allele and genotype frequencies of insulin-like growth factor-I receptor (IGF-IR) gene in two genetic groups of dairy cattle and to determine associations between this polymorphism and milk yield and milk compositions. Genomic DNA was extracted from blood and it was used for studying IGF-IR gene polymorphism by PCR-RFLP. Regarding the reports by now this gene has two alleles (A and B). Genotypes AB and BB were not detected in Holstein cows. The frequencies of genotypes AA, AB and BB in Najdi cows were 0.707, 0.293 and 0.0, respectively. Frequencies of allele A and B were 0.854 and 0.146 in Najdi, respectively. Population in the Najdi farm was in Hardy- Weinberg equilibrium. In Najdi cows, results showed no significant associations between genotypes and milk yield and milk compositions, but the effect of this polymorphism for lactation period length was significant (P < 0.05). It seems that the A allele of IGF-1R in Bos taurus descended to be fixed. Regarding the low frequency of the B allele for this gene in Najdi cows (Bos indicus), the IGF-IR gene polymorphism is not a good selection indicator for these cows. Key words: IGF-IR, PCR-RFLP, gene frequency, milk yield, lactation period length.